Coaching Model To Build Entrepreneurship Among Youth Unemployment - Hadi, Syamsul; Huda, Tanzil; Wijaya, Insan; Muhammad Iwan, Wahyudi (Journal Of Humanities Community Empowerment, 2023)
Partners often try to start building productive business, but empowerment still weak due to limited knowledge, skills, health insurance capital, technology and markets. The purpose of this program is to create a new young entrepreneurs reliable, independent and competitive among the youth unemployment. The method that used to solve the problems of these partners through the facilitation of productive economic activity based micro-scale engineering model of coaching in the form of technological and social skills through training with a participatory approach, stimulus funding and mentoring (supervision, monitoring and evaluation). Result of the evaluation of the program show that the impact of the program on the social aspects of both partners is the entrepreneurial spirit is getting stronger which can be measured in absolute numbers with Likert scale indicates the value of a score of 3.5. so it can be concluded that both partners have an entrepreneurial spirit by 75%. The impact of technological engineering shows that partners have been able to increase the procurement of oyster mushroom baglog even by purchasing, increasing turnover and expanding their marketing reach and have even diversified their business in the form of selling oyster mushroom satay. As for the impact of other social engineering is both partners have started to master the techniques of business management reasonably well and being able to access market information, read the market opportunities, technology innovations through the internet facility and has begun marketing management including control of simple bookkeeping